Relations between economic development, violence and corruption: A nonparametric approach with DEA and data panel. Issue 4 (April 2019) - Poveda, Alexander Cotte; Carvajal, Jorge Enrique Martínez; Pulido, Nicolas Ronderos
Abstract: This research analyses the connection between homicides, corruption, and economic development in Colombian government departments. This empirical research explores the trends of homicides, corruption, and economic development utilizing different estimation techniques: DEA and econometric analysis with panel data. The DEA is applied to assess socioeconomic performance and interactions of homicides, corruption, and economic progress in Colombian, according to the rank and uncertainty of corruption and violence. Econometric models are Generalized Method of Moments (GMM) estimates to determine the incidence of some institutional and socioeconomic variables on the score range of uncertainty and risk generated by DEA in terms of the level of corruption and homicides. Estimates with DEA data envelopment analysis shows that the risk score associated with homicides and corruption has different tendencies, socioeconomic and political instability are causes that explain the behaviour of this variable over time. The results of the panel data estimation show that there are several hypotheses and theories that explain the effects of corruption and violence on the economic development of countries. This finding indicates the importance of developing effective policies that strengthen public administration, the judicial structure, and public social spending and thus rupture the cycles of corruption and homicides that prevent the creation of sustained economic growth and development.